A prospective, randomised trial of different matching procedures for structured mentoring programmes in medical education. (1st September 2016) - Schäfer, Matthias; Pander, Tanja; Pinilla, Severin; Fischer, Martin R.; von der Borch, Philip; Dimitriadis, Konstantinos
Abstract: Background: Spontaneous formation of mentoring relationships can be seen as the gold standard in mentoring. Unfortunately, it happens very infrequently. The purpose of structured mentoring programmes is to facilitate the formation of mentoring relationships. This remains a challenging task, especially for large institutions. Aims: We set out to investigate and compare three methods of matchmaking in the setting of our structured mentoring programme. In a prospective, randomised trial we compared personal matching (PM) by an experienced expert to two different electronic data processing (EDP)-supported matching procedures: "online algorithm" (OA) versus "online search" (OS). Methods: PM was performed after structured interviews of prospective protégés by one founder of our mentoring programme. The OA provides students with a choice of 10 potential mentors based on comparison of online profiles. OS lets students filter and search through all available mentor profiles. One hundred and ninty medical students were randomised into the three groups. One year later, we evaluated the endpoints 1. "establishment of a mentoring relationship" and 2. "satisfaction with the mentoring relationship". Satisfaction with the mentoring relationship was assessed using Munich-Evaluation-of-Mentoring-Questionnaire (MEMeQ). Results: One hundred sixty-five out of the 190 study participants found a mentor. With regards to endpoint one we found an advantage of PM compared to both EDP-supported matching procedures. There was no significant difference between OA and OS. Concerning endpoint two the differences between the investigated matching procedures were not significant. Conclusion: PM is superior as to the number of mentoring relationships formed per participating student compared to EDP-supported methods. In our data, there was no significant difference in the level of satisfaction. Considering the high investments associated with PM of mentors and protégés, EDP-supported matching procedures seem a viable compromise between effectiveness and efficiency especially for large-scale structured mentoring programmes in medical education.